バレーボールにおける一流センタープレイヤーの4人攻撃に対するブロックに関する研究: 質的研究結果の量的方法による追研究 - 長江, 晃生; 秋山, 央; 中田, 学; 青木, 和浩; 五十嵐, 元; 中西, 康己 (コーチング学研究, 2024)
Building upon Igarashi et al.'s (2017) research, this study clarified the subjective and objective structure of blocks against four-person attacks in volleyball by top center players. We adopted a quantitative approach to investigate the relationship between the split step (SS) and block performance (BP), including committed blocks. Additionally, we examined the relationship between the quality and quantity (SS and BP) of “Kyanseru” (canceling) and “Kaijo” (releasing) by top center players during blocks against four-person attacks using inductive reasoning (a comprehensive approach). This study derived the following results: The cognitive element of anticipating the opponent's attack may lead to unconsciousness of the physical action (SS), which can be considered a technical element. This suggests that the participants' subjective and objective aspects of the “Kyanseru” and “Kaijo” may differ. Kitagawa's (a leading center player in Japan) “Kyanseru” is subjectively “always done from a committed block position.” However, “Kyanseru” can be considered to be similar to a lead block (SS with double-footed landing). Tomimatsu's (another leading center player in Japan) “Kaijo” occurs at a low rate when he is not split-stepping. “Kaijo” occurs during a right attack on double-footed SS.　These findings, which holistically analyze blocks against four-person attacks by top center players, offer novel scientific insights that can be applied by players and coaches in the field. They also exemplify how knowledge acquisition can contribute to practical application by clarifying the subjective and objective structure of blocks against such attacks.